Assessing the Alignment of Indonesia’s Green Sukuk with Maqasid Al-Shariah and ESG Principles - Ayesha Munir; Azada Razaie (Universitas Alma Ata, 2025)
Introduction: This study examines Indonesia’s sovereign green sukuk issued between 2018 and 2023, focusing on their alignment with Maqasid al-Shariah and Environmental, Social, and Governance (ESG) principles. As the first sovereign issuer of green sukuk, Indonesia provides a unique case to explore the intersection between Islamic ethical finance and global sustainability frameworks.Methodology: The research adopts a qualitative case study approach using secondary data, including Ministry of Finance allocation and impact reports, Shariah fatwas, sukuk frameworks, and third-party sustainability reviews. A hybrid analytical framework was applied, integrating Maqasid al-Shariah, ESG indicators, the Quadruple Bottom Line (QBL), and Sustainable Development Goals (SDGs).Results: The findings reveal that Indonesia’s green sukuk substantially align with Islamic ethical values and sustainability targets. Projects financed through these sukuk avoided an estimated 12.2 million tons of CO₂-equivalent emissions, added more than 15 MW of renewable energy capacity, and restored over 10,000 hectares of degraded land. Socially, the sukuk program benefited approximately 4.2 million people through access to clean water, disaster-resilient facilities, and sustainable transport. Governance mechanisms such as annual reporting and Second Party Opinions ensure transparency, while spiritual compliance is maintained through continuous supervision by DSN-MUI.Conclusion: Indonesia’s sovereign green sukuk demonstrate the potential of Shariah-compliant instruments in advancing climate finance. However, challenges remain in addressing regional equity, enhancing participatory governance, and integrating long-term spiritual and social indicators. Strengthening these aspects could position Indonesian green sukuk as a global model for Islamic sustainable finance.